Influence of pure oxygen on nanostructure of water-soluble pectin in pear (Pyrus bretschneideri Rehd cv. Huangguan) - Lin, Min; Deng, Yun; Xiao, Chenlong; Liu, Mingyang; Zhu, Liwei; Luo, Wen; Yang, Hongshun (2010)
The effects of pure oxygen and storage time on nanostructure degradation of water-soluble pectin (WSP) in pear (Pyrus bretschneideri Rehd cv. Huangguan) were examined during 30 d of storage in air (control) and pure oxygen at 2 C and 95% relative humidity. Qualitative and quantitative information on WSP polymers was determined by atomic force microscopy (AFM) on days 0, 10 and 30. Results showed that the frequency of small width WSP increased in all treatments over storage time, but was higher in the control, indicating pure oxygen treatment inhibited the degradation of WSP molecules and the aggregate separation. Widths of WSP chains consisted of three basic units with widths of 15.625, 23.438 and 58.594 nm obtained from AFM determination. Data obtained in this study suggest that the fundamental structure of the WSP molecule consists of parallel linkages or intertwists between the basic units.
Keywords: Pears; Chemical properties; Food storage